The enhanced heat source model and its verification of unsteady heat transfer simulation in laser quenching based on experiment - Yutong Guo; Gangyan Li; Rui Shen; Hui Shi; Baoming Hu (Case Studies in Thermal Engineering)
Laser hardening, also known as laser phase transformation hardening, is a critical surface modification technology. In current engineering practice, the design of process parameters primarily relies on simulation. However, variations in actual conditions pose a significant challenge in selecting the most appropriate heat source model for accurately simulating the laser quenching process. This paper proposes a novel heat source model calculation method for simulation analysis by integrating the weighted residual Galerkin method with matrix block computation, based on temperature data acquired from the upper surface during laser quenching. By comparing the three-dimensional numerical simulation results of the transient heat transfer process of laser quenching using the proposed surface heat source model with experimental measurements obtained under corresponding conditions, it is demonstrated that the heat source model derived from this method achieves superior accuracy compared to traditional empirical models within the experimental environment utilized in this study. Furthermore, the simulation accuracy of the heat source model obtained through this computational approach remains consistently below 5 %, exhibiting minimal fluctuation even when laser power, laser state, and sample thickness vary.